2021
DOI: 10.1038/s41467-021-27234-3
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses identify DNA methylation associated with kidney function and damage

Abstract: Chronic kidney disease is a major public health burden. Elevated urinary albumin-to-creatinine ratio is a measure of kidney damage, and used to diagnose and stage chronic kidney disease. To extend the knowledge on regulatory mechanisms related to kidney function and disease, we conducted a blood-based epigenome-wide association study for estimated glomerular filtration rate (n = 33,605) and urinary albumin-to-creatinine ratio (n = 15,068) and detected 69 and seven CpG sites where DNA methylation was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 89 publications
1
42
0
Order By: Relevance
“…Sometimes, the CpG site correlated with multiple genes in cis. Schlosser et al [27] also observed the impact of DNA methylation at cg04864179 on IRF5 transcript levels, which might subsequently affect eGFR. Colocalization of IRF5 gene expression with eGFR has been reported in blood as well as tubular and glomerular compartments of kidney tissue [86].…”
Section: Dna Methylation Impact On Egfrmentioning
confidence: 97%
See 4 more Smart Citations
“…Sometimes, the CpG site correlated with multiple genes in cis. Schlosser et al [27] also observed the impact of DNA methylation at cg04864179 on IRF5 transcript levels, which might subsequently affect eGFR. Colocalization of IRF5 gene expression with eGFR has been reported in blood as well as tubular and glomerular compartments of kidney tissue [86].…”
Section: Dna Methylation Impact On Egfrmentioning
confidence: 97%
“…Therefore, it is plausible that alterations in EBF1 gene methylation may be related to kidney damage. In turn, Schlosser et al [27] identified changes in methylation patterns in 69 CpGC related to eGFR, and 65 of them were also observed in CKD patients. Moreover, the methylation of CpGs cg18194850 in SUCLG2 gene and cg07242931 in MAN1C1 gene correlated not only with eGFR but also with time to kidney failure or acute kidney injury [27].…”
Section: Dna Methylation Impact On Egfrmentioning
confidence: 99%
See 3 more Smart Citations